Star trek. Volume 6, After darkness - Johnson, Mike (Comic book author) (IDW, 2013)
Picking up where the motion picture Star trek into darkness left off, this volume follows the U.S.S. Enterprise as it embarks on a new five-year mission of exploration. In this installment, Spock undergoes a disastrous episode of Pon Farr, the Enterprise investigates a colony allegedly wiped out by the Gorn, and tensions continue to escalate between the Federation and Klingons.